Members of the Trichoderma harzianum Species Complex with Mushroom Pathogenic Potential - Henrietta Allaga; Anuar Zhumakayev; Rita Büchner; Sándor Kocsubé; Attila Szűcs; Csaba Vágvölgyi; László Kredics; Lóránt Hatvani (Agronomy, 2021)
Previously, severe green mould infections could be attributed mainly to Trichoderma aggressivum Samuels & W. Gams, as well as T. pleuroti S.H. Yu & M.S. Park and T. pleuroticola S.H. Yu & M.S. Park in the case of Agaricus bisporus (J.E. Lange) Imbach (button mushroom) and Pleurotus ostreatus (Jacq.) P. Kumm. (oyster mushroom), respectively. The purpose of our study was the examination of green mould agents deriving from the growing facilities of button mushroom, oyster mushroom and shiitake (Lentinula edodes (Berk.) Pegler) located in various countries of Europe, and initially classified into the Trichoderma harzianum Rifai species complex (THSC). Species identification was carried out using the multilocus sequence typing analysis of the internal transcribed spacer regions, as well as translation elongation factor 1-alpha, calmodulin and RNA polymerase B subunit II gene sequences. In vitro confrontation assays were applied to test the aggressiveness of the isolates towards mushrooms, while the effect of commercial fungicides on the growth of the strains was examined by the macrodilution method. Six Trichoderma species, namely T. afroharzianum P. Chaverri, F.B. Rocha, Degenkolb & Druzhin., T. atrobrunneum F.B. Rocha, P. Chaverri & Jaklitsch, T. guizhouense Q.R. Li, McKenzie & Yong Wang, T. harzianum sensu stricto, T. pollinicola F. Liu & L. Cai and T. simmonsii P. Chaverri, F.B. Rocha, Samuels, Degenkolb & Jaklitsch were detected in the different samples, with T. harzianum, T. pollinicola and T. simmonsii being the most aggressive. Prochloraz was found to have strong in vitro inhibitory effect on mycelial growth on most strains, however, T. simmonsii isolates showed remarkable tolerance to it. Our data suggest that T. harzianum and T. simmonsii may also be considered as potential causal agents of mushroom green mould.